Aria dla atlety - Bajon, Filip; Zielinski, Jerzy; Majchrzak, Krzysztof; Raksa, Pola; Wilhelmi, Roman
Set at the turn of the century it presents a story of a famous Polish athlete, Zbyszko Cyganiewicz. It begins in a small town where a traveling circus attracts a shy boy into a phony wrestling game to please the crowds. The youth, however, takes his strength seriously, eventually defeating a name wrestler in a fair match. Angered circus manager fires him; he leaves happily due to two wrestler brothers who were harassing him. The wrestler goes on to fame, performing in the world's top arenas, and one day is serenaded by a tenor from the crowd. Fame brings him women and admirers but he is uncompromising on his profession. He has his revenge on one of his tormentors defeating him in the ring. One day, attending a game in a tuxedo, he is challenged by another of the brothers and drawn into a brutal game, in course of which he kills his opponent. Thus his career ends. [Polish Cinema Database]
Keywords: DVD-Video